PENGARUH ADVERSITY QUOTIENT, REGULASI DIRI DAN EFIKASI DIRI TERHADAP MOTIVASI BERPRESTASI SISWA KKO SMP NEGERI 13 YOGYAKARTA - Erlin Dwi Kusumawati (Department of Islamic Education, The State Islamic University Sunan Kalijaga Yogyakarta, 2017)
This research aims to understand the influence of adversity quotient, self regulations and self efficacy against acievement motivation performed on students of special class of sports (KKO) of 13 Yogyakarta junior high school. Hypothesis advanced by is that there is the positive influence andsignificant between adversity quotient, self regulations and self efficacy against acievement motivation. The research is research regression analysis with the quantitative approach. As for population in this research is all students a special class of sports 13 Yogyakarta junior high schools were 87 students. Data collection method the main used in this research using scale and will be analized by using some help application IBM SPSS statistisc 19. The result showed the positive influence and significant between adversity quotient, self regulations and self efficacy of outstanding the motivation students of special class sports (KKO) 13 yogyakarta junior high school. Adversity quotient (x1) contributed for 44.6%, self regulations (x2) of 47.8% , then the self efficacy (x3) of 49.2%, and contribution to all variable in this research on achievement motivation representatives of 65.6%. The rest of 34.4% influenced by other variables outside the research.